The perfume of the lady in black - Leroux, Gaston, 1868-1927; Simont (Salt Lake City, UT : Project Gutenberg, 2025)
"The Perfume of the Lady in Black" by Gaston Leroux is a novel written in the early 20th century. The story revolves around the aftermath of a wedding between Robert Darzac and Mathilde Stangerson, taking place in a shadowy, foreboding church. The main character, Joseph Rouletabille, a young and clever reporter, is expected to play a pivotal role in unraveling the mystery surrounding the couple's past and a lurking threat that could disrupt their newfound happiness. The opening of the novel presents a wedding marked by an atmosphere filled with unease and fear, as characters express their lingering concerns about Frederic Larsan, a presumed dead enemy linked to a traumatic past event. The wedding attendees, especially Rouletabille, are caught in a whirlwind of emotions, with the absence of Rouletabille noted when Mathilde seeks him out in distress. His unexplained disappearance evokes worry, hinting at a greater mystery at play. Additionally, the text unveils Rouletabille's complicated feelings towards Mathilde and his past encounters with her, suggesting a layered narrative that intertwines themes of love, loss, and the pursuit of truth as the story develops. (This is an automatically generated summary.)
Wikipedia page on this work: https://en.wikipedia.org/wiki/The_Perfume_of_the_Lady_in_Black_(novel)
Release date is 2025-01-31
Aaron Adrignola, Laura Natal, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Detective and mystery stories; Rouletabille, Joseph (Fictitious character) -- Fiction